AN ACTION RESEARCH PROJECT: STUDENTS’ RESPONSES TO AND PERCEPTIONS OF TRAINING TO DEVELOP EFFECTIVE VOCABULARY LEARNING STRATEGIES - Blanco-Hermida, María; Úbeda Mansilla, Paloma (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This article reports on a small-scale action research study aimed at exploring the impact of vocabulary learning strategies (VLS) awareness-raising and training sessions on two groups of Spanish as a Foreign Language beginners. The exploration focused on identifying changes to strategy use and students’ experience of strategy effectiveness after a series of VLS awareness-raising and training sessions that took place on a Spanish beginners’ course. In addition, feedback on the sessions was sought from the students. Data were collected through semi-structured questionnaires and interviews. Responses from the participants were coded using an adaptation of VLS from Schmitt, N. (1997) classification: additional VLS that emerged from the data was also added. Emergent themes from the questionnaires and interviews were analyzed and included in the findings. The results revealed changes in strategy use and suggest that students benefited from the VLS awareness-raising and training sessions. Furthermore, the results provide insights into factors that affect strategy effectiveness and students’ perceptions of what made strategies particularly effective for them when learning Spanish.